Psychopathology in childrens of type i and type ii alcoholic’s - Akbaş, Seher; Tütüncü, Emel; Tamar, Müge; Coşkunol, Hakan; Kesikçi, Hande (Journal of Dependence, 2004)
Objective: In this study, we investigated psychopathology in children of Type I and Type II alcoholics. The relationship between father’s alcoholism type and co-morbidity and the psychopathology in their children is investigated. Method: Socio-demographic Data Form, Michigan Alcoholism Screening Test (MAST) and SCID-I were applied to alcoholics fathers in early complete remission after detoxification treatment in the alcohol and drug addiction unit of the Ege University Medical Faculty. We determined fathers alcoholism types in the unit by evaluating the data we had got and by Cloninger’s alcoholism typology. Psychiatric interviews were made with 8-12 years children of these fathers according to the DSM-IV criteria and CDI ( Children Depression Inventory) and socio-demographic data forms were filled. Results: The study was made with 25 Type I alcoholics 10 Type II alcoholics and in same numbers of their 8-12 year-old children. no relationship was observed between fathers’ Type I and Type II alcoholism and children’s psychiatric diagnoses. There was also no relationship between fathers’ alcoholism severity and children’s psychiatric diagnoses. There was, however, relationship observed between co-morbidity in fathers and an increased level of psychopathology in children. Conclusion: In our study, children of alc0holics were affected by parents’ co-morbid psychiatric disorders. For this reason, the clinician should be aware of children’s psychopathology in the presence of alcoholic parents’ co-mor-bidity.